The Development of Cooperative Professional Supervision Model for Improving English Teachers’ Teaching Quality - Prathumchai, Ampha; Namwan, Tharinthorn; Ruannakarn, Praseart (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this research were: to study the current situation and need for model, model development, model trying out, and evaluation of application in Cooperative Professional Supervision Model for improving the English teacher’s Teaching Quality by using Research and Development. There were 4 Phases of this research. Phase 1, the current situation and need for Supervision Model, were studied by asking from 400 schools. Phase 2, the Cooperative Professional Supervision Model was studied from 3 Best Practice Schools. The tentative model was outlined through Focus Group Discussion by 10 experts and coworkers. It was tried out in 2 schools. The model was evaluated by the experts. The research instruments were: the Interview Form, Questionnaire, and Evaluation Form. Phase 3, the model was tried out with 2 schools. The research instruments were: the Handbook of Model Application, Knowledge Test, and Satisfaction Questionnaire. Phase 4, the model was evaluated by the model users and experts. The research instruments were: the Satisfaction Questionnaire and Model Quality Evaluation. The statistic using for data analysis included the percentage, Mean, Standard Deviation, t-test, and Content Analysis. The research findings found that the current situation of instructional implementation was in “High” level. However, it was the overall supervision in every subject. They showed their need for the Cooperative Professional Supervision Model especially in English Language Subject. There were 5 components of the Cooperative Professional Supervision Model including: the principle of model, objective, knowledge management process, model evaluation, condition of success. Besides, there were 5 steps of supervision process including: the work implementation planning, knowledge promotion before supervision, construction of team working for supervision practice, work performance evaluation, and magnification of findings. Trying out the Cooperative Professional Supervision Model, the students improved their learning achievement in English Language. The English teachers using and the model users expressed their satisfaction on the model in “High” level. The experts evaluated the model in “the Highest” level.